PENAFSIRAN DI BALIK PENAMAAN HANTU DI MAJALENGKA JAWA BARAT - Rawinda Fitrotul Mualafina (Universitas PGRI Semarang, 2013)
Local wisdom is one of culture product which appear from interpretation of social phenomenon, including language phenomenon. One of them is that found in Majalengka. On that society was found some ghost names lexicon that are believed to be around them. In this article entitled ?óÔé¼?ôInterpretatin Behind Majalengka West Java Ghost Naming?óÔé¼?Ø presented a number of interpretations related to ghost names lexicon are not only being present as a series of its vocabularies, but also as series of local wisdom which held by the community. This is evident from other education and other culture interpretation implicity contained behind the ghost naming. Keyword: ghosts lexicon, ghost name, majalengka, education